An immunoperoxidase study of epithelial marker antigens in ulcerative colitis with dysplasia and carcinoma. Issue 1 (January 1985) - Allen, D C; Biggart, J D; Orchin, J C; Foster, H
Abstract : An immunoperoxidase technique was applied to formalin and Helly fixed paraffin wax sections from cases of ulcerative colitis complicated by dysplasia and carcinoma for carcinoembryonic antigen and components of the colonic secretory immunoglobulin system--namely, secretory component, IgA, and J chain. Sections from both resection specimens and mucosal biopsies were available. Intensity of immunostaining was assessed qualitatively. There was appreciable variation in expression of carcinoembryonic antigen and secretory component antigens. Carcinoembryonic antigen stained heavily in dysplasia and carcinoma while these tissues showed only focal light staining for secretory component. Normal tissue stained heavily for secretory component. The variation in staining intensity for both carcinoembryonic antigen and secretory component in inflamed and regenerative mucosa precluded their use as a reliable diagnostic aid in discriminating these tissues from true dysplasia. Loss of secretory component production or transport or both may be incurred during malignant change, but it should not be assessed as an isolated index of epithelial maturity. The relation with mucosal plasma cells warrants further study to determine more fully the factors affecting tissue secretory component expression.